Two‐dimensional and shear wave elastography ultrasound: A reliable method to analyse spastic muscles?. Issue 2 (3rd July 2017) - Mathevon, Laure; Michel, F.; Aubry, S.; Testa, R.; Lapole, T.; Arnaudeau, L. F.; Fernandez, B.; Parratte, B.; Calmels, P.
ABSTRACT: Introduction: Few data exist on the feasibility and reliability of measuring muscular atrophy in 2 dimensions (2D) by ultrasonography (US) and elasticity with shear wave elastography (SWE) in spastic muscles. Methods: Fourteen patients with chronic stroke took part in 2 intersession reliability experiments performed with 1‐week intervals between sessions. Pennation angle (PA), muscle thickness (MT), and shear elastic modulus (µ) were measured in spastic gastrocnemius medialis (GM) muscles at rest and at maximal passive stretching in paretic and nonparetic legs. Results: On the paretic side, the coefficient of variation (CV) in GM was 6.30% for MT and 6.40% for PA at rest and was 7.53% and 8.26% for MT and PA, respectively, at maximal passive stretching. The reliability of the µ measurement was good only for GM at rest on the paretic side (CV = 9.86%). Discussion: 2D US associated with SWE shows promise for assessing structural changes in muscles. With some methodological adaptations, this approach could help guide spasticity treatment. Muscle Nerve 57 : 222–228, 2018